Pendekatan Retoris Dan Relasional Di Taman Pendidikan Al-Quran Darul Hamdi 2 - Sari, Dina Emilia (Tuturlogi: Journal of Southeast Asian Communication, 2022)
All human activities always have a communication aspect in it. One of them is in the field of instructional. In the 1970s, instructional communication focused on the role of communication in teaching. Previous researchers revealed that teachers should not only focus on understanding the material but also how to create a sense of comfort for students. This approach comes from the Rhetorical and Relational Goal Theory. This study looks at how the rhetorical and relational approaches are used during the learning process at TPQ Darul Hamdi 2. This research is a qualitative research with an interpretative paradigm. The research was conducted by observing. Participants were selected by purposive sampling technique. The results of this study indicate that TPQ Darul Hamdi 2 applies the demonstrating instructional strategy by Clarissa Gomes Foletto as a rhetorical approach and focuses on classroom interaction, teacher attitudes, child independence, and teacher-student relationships as a relational approach. Based on data analysis, the approaches taken are effective in learning even though there are several efforts that need to be corrected and increased again.